Audit Pricing, Lowballing and Auditor Turnovers: A Dynamic Analysis. - Kanodia, Chandra; Mukherji, Arijit (The Accounting Review, 1994)
Abstract Analyzes audit pricing, lowballing and auditor turnover services in accounting practices. Insight into audit pricing model; Effect of lowballing to auditor independence; Evolution of audit prices and auditor turnover; Empirical implications.